2021
DOI: 10.1016/j.ijrobp.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocytes in Low-Risk Patients With Breast Cancer Treated With Single-Dose Preoperative Partial Breast Irradiation

Abstract: Preoperative partial breast irradiation (PBI) has the potential to induce tumor regression. We evaluated the differences in the numbers of preirradiation tumor infiltrating lymphocytes (TILs) between responders and nonresponders after preoperative PBI in low-risk patients with breast cancer. Furthermore, we evaluated the change in number of TILs before and after irradiation. Methods and Materials: In the prospective ABLATIVE study, low-risk patients with breast cancer underwent treatment with single-dose preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The differences in the numbers of pre-irradiation tumour infiltrating lymphocytes (TILs) between responders and non-responders after preoperative PBI in low-risk patients with breast cancer was also evaluated (22 pairs of pre-irradiation and post-irradiation tissue available). After preoperative PBI in this limited cohort, the number of TILs in tumour tissue decreased, although no differences in numbers of pre-irradiation TILs between responders and non-responders were observed [20] .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The differences in the numbers of pre-irradiation tumour infiltrating lymphocytes (TILs) between responders and non-responders after preoperative PBI in low-risk patients with breast cancer was also evaluated (22 pairs of pre-irradiation and post-irradiation tissue available). After preoperative PBI in this limited cohort, the number of TILs in tumour tissue decreased, although no differences in numbers of pre-irradiation TILs between responders and non-responders were observed [20] .…”
Section: Discussionmentioning
confidence: 61%
“…High dose gradient techniques, such as stereotactic body radiation therapy (SBRT), have been routinely implemented in clinical practice thanks to their widespread availability, and are currently used as a curative treatment in several diseases (i.e., non-small cell lung cancer, prostate cancer) [14] , [15] . Several studies assessed the feasibility of PBI using multiple techniques in the preoperative setting followed by standard BCS [16] , [17] , [18] , [19] , [20] . Cyberknife® (Accuray Incorporated, Sunnyvale, CA, USA) is a frameless robotic stereotactic radiosurgery system, providing continuous motion tracking during respiratory movement.…”
Section: Introductionmentioning
confidence: 99%
“…A 5-fraction schedule is the standard regimen and probably the appropriate compromise in terms of efficacy, safety, and HRQoL,10 also considering the negative results of most intraoperative single-fraction PBI trials 11–16. A new frontier is now open on the potential benefit of preoperative PBI delivery,17 although concerns remain on the optimal dose, fractionation, and technique 18–23. Therefore, postoperative PBI still represents the gold-standard of treatment.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…[11][12][13][14][15][16] A new frontier is now open on the potential benefit of preoperative PBI delivery, 17 although concerns remain on the optimal dose, fractionation, and technique. [18][19][20][21][22][23] Therefore, postoperative PBI still represents the gold-standard of treatment. One of the most exciting perspectives is based on trials evaluating the optimization of all adjuvant treatments for lowrisk breast cancer, including but not limited to RT.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In the ABLATIVE trial, 67% of patients with rCR had a pCR and 33% had near pCR after 6 to 8 months (22). Additionally, the prediction of pCR after pre-operative systemic therapy using liquid biopsies and biomarkers in tumor tissue, such as tumor-in ltrating lymphocytes (TILs), have been evaluated, and to a much lesser extent after pre-operative RT (22,(30)(31)(32). The ABLATIVE trial showed presence of TILs preirradiation and 6 to 8 months post-irradiation (30).…”
Section: Introductionmentioning
confidence: 99%